Colorimetric and ratiometric sensors derivated from natural building blocks for fluoride ion detection. Issue 52 (26th December 2019) - Shi, Heng; Zhao, Fengfei; Chen, Xinghan; Yang, Shilong; Xing, Jieni; Chen, Hongjin; Zhang, Rui; Liu, Jian
Graphical abstract: Highlights: Three novel probes were synthesized from flavone and natural phenylacrylic acids. SH-1 3 were developed as colorimetric and ratiometric sensors for F − detection. Probes SH-1 3 showed high sensitivity and selectivity for F − detection. Abstract: Three novel colorimetric and ratiometric probes (SH-1 3 ) for fluoride ion detection were designed and synthesized from nature small molecules. Obvious yellow-to-orange color change of these probes in the THF was achieved only in presence of F − among the eight anions (F −, Cl −, Br −, I −, H2 PO4 −, HSO4 −, CH3 COO –, ClO4 − ), along with the emission shifting from green to orange red. These three probes are 1:1 complexed with fluoride ions, with complexation constant of around 0.1 × 10 4 M −1 . The detection limit of probes SH-1 3 reached as low as around 1 μM. 1 H NMR titration study suggested that the fluoride ion induced deprotonation of the probe through hydrogen bonding interaction between amino group of probe and fluoride ion.